The Relationship Between Care Environment Stressors with Oxygen Saturation and Quality of Life of Covid-19 Patients - Suhariyati Suhariyati; Abdul Rokhman; Dias Tiara Putri Utomo; Arifal Aris; Siti Sholikhah (Universitas Muhammadiyah Jember, 2021)
Coronavirus disease 2019 (COVID-19) is an infectious disease which causes respiratory problems, acute respiratory syndromes, kidney failure, and even death. This research aimed to investigate the relationship between care environment stressors with oxygen saturation and quality of life of COVID-19 patients in isolation rooms of dr. Soegiri hospital Lamongan. The research applied a correlational design and conducted in isolation rooms of dr. Soegiri hospital Lamongan. The samples were 59 respondents who were obtained by purposive sampling. The data were gathered from March to May 2021. The research variables included care environment stressors, oxygen saturation, and quality of life. The instrument was a questionnaire. The data were analyzed by Gamma and Somers tests (α = 0.05). The research results showed that care environment stressors significantly related to oxygen saturation and quality of life (p 0.05). It is hoped that families and health workers will always provide support to COVID-19 patients who are being treated in isolation rooms. Further research is needed.